Immunohistological composition of peri‐implantitis affected tissue around ceramic implants—A pilot study. Issue 4 (17th September 2020) - Fretwurst, Tobias; Müller, Janina; Larsson, Lena; Bronsert, Peter; Hazard, Derek; Castilho, Rogerio M.; Kohal, Ralf; Nelson, Katja; Iglhaut, Gerhard
Abstract: Background: Aim of the pilot study was the histologic classification of the inflamed peri‐implant soft tissue around ceramic implants (CI) in comparison with titanium implants (TI). Methods: Peri‐implant tissue were retrieved from 15 patients (aged 34 to 88 years, seven males/eight females) with severe peri‐implantitis (eight CI, seven TI). The peri‐implant soft tissue samples were retrieved from the sites during scheduled removal of the implant and prepared for immunohistochemical analysis. Monoclonal antibodies (targeting CD3, CD20, CD138, and CD68) were used to identify T‐ and B‐cells, plasma cells and macrophages. Quantitative assessment was performed by one histologically trained investigator. Linear mixed regression models were used. Results: A similar numerical distribution of the cell population was found in peri‐implantitis around CI compared with TI. CD3 (TI, 17% to 85% versus CI, 20% to 70% of total cell number) and CD138 (TI, 1% to 73% versus CI, 12% to 69% of total cell number) were predominantly expressed. Notably, patient‐individual differences of numerical cell distribution were detected. Co‐localization of B‐ and T‐lymphocytes was observed. Conclusions: Peri‐implantitis around CI in comparison with TI seems to have a similar histological appearance. Differences in cellular composition of peri‐implantitis lesions might also depend on the patient's specific immune status and not only on the material used.